THE VALUE OF LIFE GAINED FROM SENO GUMIRA AJIDARMA'S "TRILOGI ALINA" THROUGH ROLAND BARTHES’ SEMIOLOGICAL STUDY - Inez Alvisari; Nurholis H (Linguistics and Literature Students' Journal, 2023)
Every short story by Seno Gumira Ajidarma in the anthology “Sepotong Senja untuk Pacarku” uses the same theme of twilight with its reddish light and seaside nuances, including the three short story collections to be discussed, the Alina Trilogy.  Many readers manifest their lover's shadow into the character of Alina in the short story "Sepotong Senja untuk Pacarku" which takes Sukab's point of view since Ajidarma released it in 1991 This research uses a subjective approach and descriptive subjective research method that is interpretive. The subject to be researched in this research is Seno Gumira Ajidarma's short story "Alina Trilogy" which is a series of three short stories completed by Seno Gumira Ajidarma over ten years. The first story is "Sepotong Senja Untuk Pacangu" which he completed in 1991, and 10 years later, in 2001, a connection was made to this short story with the title "Jawaban Alina" and "Tukang Pos dalam Amplop" in the same year. The research will use the constructivism paradigm and will be described with descriptive semiotics and/or a little hermeneutics. Meanwhile, the data collection technique will be done by document study and internet search. This research aims to find out what meanings are contained in the short story "Alina's Trilogy" and draw the value of life in it.Keywords: Alina, Ajidarma, Barthes, Trilogy Alina